6(-4+5h-5-3h)=

Simple and best practice solution for 6(-4+5h-5-3h)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-4+5h-5-3h)= equation:


Simplifying
6(-4 + 5h + -5 + -3h) = 0

Reorder the terms:
6(-4 + -5 + 5h + -3h) = 0

Combine like terms: -4 + -5 = -9
6(-9 + 5h + -3h) = 0

Combine like terms: 5h + -3h = 2h
6(-9 + 2h) = 0
(-9 * 6 + 2h * 6) = 0
(-54 + 12h) = 0

Solving
-54 + 12h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + 12h = 0 + 54

Combine like terms: -54 + 54 = 0
0 + 12h = 0 + 54
12h = 0 + 54

Combine like terms: 0 + 54 = 54
12h = 54

Divide each side by '12'.
h = 4.5

Simplifying
h = 4.5

See similar equations:

| 6[6-(-7x-3)]=168x+108 | | 3n^2+9x+9=3 | | 3x-0.1=0.2-0.4(7-2x) | | 2x/2=0/2 | | 13-2m=19 | | 9x+36=81 | | 8x-12-5x+7=19 | | 4a+15bc+12b+5ac= | | 4(x+2x)=-24 | | -9x+9y=-5-3y | | b-6.2=-8 | | 8x-2(4+3x)=3x | | 4k+44=10-10 | | 3x+-7=5x+13 | | .15=.042+1.8(x-.042) | | 2x-5(x-2)=-3+5x-19 | | -8(v+4)+2v+5=6v+11 | | 1.2x+3=7 | | 98=1x+2.5y | | 20x-10=5x+2 | | 98=2x+2y | | -2.4+0.4v=16 | | 8x-2(4+3x)= | | 3x^2+18x+36=0 | | x+3=27x^2 | | -0.6(2x-8)=1.3(4-x) | | .15=1.842(x-.042) | | 2(x-2)=2(3x+1)+2 | | g+(-2.3)=9.5 | | -47=(2x+1)+3 | | 40Prt=i | | 17x-2y=-19 |

Equations solver categories